Design and Evaluation of a Pressure and Temperature Monitoring System for Pressure Ulcer Prevention - Farve Daneshvar Fard; Sahar Moghimi; Reza Lotfi (Iranian Journal of Medical Physics, 2014)
Introduction Pressure ulcers are tissue damages resulting from blood flow restriction, which occurs when the tissue is exposed to high pressure for a long period of time. These painful sores are common in patients and elderly, who spend extended periods of time in bed or wheelchair. In this study, a continuous pressure and temperature monitoring system was developed for pressure ulcer prevention. Materials and Methods The monitoring system consists of 64 pressure and 64 temperature sensors on a 40×50 cm2 sheet. Pressure and temperature data and the corresponding maps were displayed on a computer in real-time. Risk assessment could be performed by monitoring and recording absolute pressure and temperature values, as well as deviations over time. Furthermore, a posture detection procedure was proposed for sitting posture identification. Information about the patient’s movement history may help caregivers make informed decisions about the patient’s repositioning and ulcer prevention strategies. Results Steady temporal behaviour of the designed system and repeatability of the measurements were evaluated using several particular tests. The results illustrated that the system could be utilized for continuous monitoring of interface pressure and temperature for pressure ulcer prevention. Furthermore, the proposed method for detecting sitting posture was verified using a statistical analysis. Conclusion A continuous time pressure and temperature monitoring system was presented in this study. This system may be suited for pressure ulcer prevention given its feasibility for simultaneous monitoring of pressure and temperature and alarming options. Furthermore, a method for detecting different sitting postures was proposed and verified. Pressure ulcers in wheelchair-bound patients may be prevented using this sitting posture detection method.